2008
DOI: 10.1007/s11882-009-0007-4
|View full text |Cite
|
Sign up to set email alerts
|

Oral immunotherapy for food allergy

Abstract: Current management of food allergy involves strict avoidance, education on recognizing and managing allergic reactions, and carrying an adrenaline autoinjector. This approach is burdensome and associated with reduced quality of life. Patients with food allergy would benefit greatly from a treatment that could achieve desensitization or long-term tolerance. Recent studies have shown that oral immunotherapy (OIT) can induce desensitization and modulate allergen-specific immune responses; however, it remains unce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…19,[123][124][125][126][127][128] Systematic reviews have tried to focus onto the issue and shed a light about current approaches in diagnosing and managing food allergy. 129 In peanut allergy, for example, many efforts have been recently made, 120,123,130 albeit doubts remain about reliability and clinical effectiveness of peanut allergy oral immunotherapy (OIT).…”
Section: Immunotherapy With Allergens and Bat: Oral Immunotherapy (Oimentioning
confidence: 99%
See 1 more Smart Citation
“…19,[123][124][125][126][127][128] Systematic reviews have tried to focus onto the issue and shed a light about current approaches in diagnosing and managing food allergy. 129 In peanut allergy, for example, many efforts have been recently made, 120,123,130 albeit doubts remain about reliability and clinical effectiveness of peanut allergy oral immunotherapy (OIT).…”
Section: Immunotherapy With Allergens and Bat: Oral Immunotherapy (Oimentioning
confidence: 99%
“…In subjects who develop food allergy, there is a failure or loss of oral tolerance acquisition to a limited number of food allergens. OIT may offer a promising approach to induce specific oral tolerance to selected food allergens, though yet restricted to a small group of molecules, and can represent a potential strategy for long-term curative treatment of food allergy, 125 though many controversial problems about protocol and allergen dose yet exist, even for other AIT protocols. [143][144][145][146][147][148][149][150] The application of BAT in oral immunotherapy should consider also the role of secretory IgAs and their receptor on granulocytes.…”
Section: Immunotherapy With Allergens and Bat: Oral Immunotherapy (Oimentioning
confidence: 99%
“…OIT can be performed via a rush protocol in a hospital setting or more slowly as an outpatient. Studies have shown that OIT can promote desensitization to milk, egg and peanut-allergic children even in cases of severe reactions marked by tolerance of larger amounts of food allergen and reduced allergenspecific IgE [38][39][40][41][42][43][44][45]. In a recent OIT follow-up study, six out of 13 patients with severe milk allergy tolerated milk doses as high as 16 000 mg of milk protein (16 ounces of milk) without a reaction.…”
Section: Oral Immunotherapymentioning
confidence: 99%
“…Recent advances regarding the complex pathogenesis of the disease shows that it is the result of the loss or lack of achieving oral tolerance to food allergens (3).…”
mentioning
confidence: 99%